Am Puls des deutschen Wohnimmobilienmarktes: Vom Ölpreisschock bis zur Flüchtlingskrise - Norbert Hiller; Sören Gröbel (Wirtschaftsdienst, 2016)
In seiner jüngeren Geschichte war Deutschland mit vielen tiefgreifenden ökonomischen Krisen konfrontiert. Diese wirkten sich vollkommen unterschiedlich auf den Wohnimmobilienmarkt aus. Einige Krisen machten sich auf nationaler, andere hingegen lediglich auf regionaler Ebene bemerkbar. Manche Krisen wiederum gingen scheinbar spurlos am deutschen Wohnimmobilienmarkt vorbei. – – In its recent history, Germany has faced many serious economic crises. Remarkably, these crises all had a completely different impact on local housing markets. Some crises occurred at the national level, while others only took place at the regional level. Interestingly some crises were seemingly unnoticed by the German housing market. Hence, the question arises why the German housing market reacted differently to these crises and to what extent economic policy decisions were involved.
Keywords: N00; R31; R38; 330; Wohnungsmarkt; Wohnungsbestand; Wirtschaftskrise; Wirkungsanalyse; Deutschland